The influence of circular RNAs on autophagy and disease progression. Issue 2 (1st February 2022) - Wang, Yian; Mo, Yongzhen; Peng, Miao; Zhang, Shanshan; Gong, Zhaojian; Yan, Qijia; Tang, Yanyan; He, Yi; Liao, Qianjin; Li, Xiayu; Wu, Xu; Xiang, Bo; et al.
ABSTRACT: Circular RNAs (circRNAs) are non-coding RNAs that have attracted considerable attention in recent years. Owing to their distinct circular structure, circRNAs are stable in cells. Autophagy is a catabolic process that helps in the degradation and recycling of harmful or inessential biological macromolecules in cells and enables cells to adapt to stress and changes in the internal and external environments. Evidence has shown that circRNAs influence the course of a disease by regulating autophagy, which indicates that autophagy is involved in the onset and development of various diseases and can affect drug resistance (for example, it affects cisplatin resistance in tumors). In this review, we summarized the role of circRNAs in autophagy and their influence on disease onset and progression as well as drug resistance. The review will expand our understanding of tumors as well as cardiovascular and neurological diseases and also suggest novel therapeutic strategies. Abbreviations : ACR : autophagy-related circRNA; ADSCs: adipogenic mesenchymal stem cells; AMPK: AMP-activated protein kinase; ATG: autophagy related; BCL2: BCL2 apoptosis regulator; BECN1: beclin 1; ceRNA: competing endogenous RNA; circRNA: circular RNA; CMA: chaperone-mediated autophagy; EPCs: endothelial progenitor cells; LE/MVBs: late endosomes/multivesicular bodies; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; NSCLC: non-small cell lung cancer; PDLSCs: periodontal ligament stem cells; PE: phosphatidylethanolamine; PtdIns: phosphatidylinositol; PtdIns3K: phosphatidylinositol 3-kinase; PtdIns3P: phosphatidylinositol-3-phosphate 1, 2-dipalmitoyl; PTEN: phosphatase and tensin homolog; RBPs: RNA-binding proteins; SiO2 : silicon dioxide; TFEB: transcription factor EB; ULK: unc-51 like autophagy activating kinase 1